NFLASI DI INDONESIA PADA PERIODE 2011-2015: ANALISIS SERTIFIKAT BANK INDONESIA, SERTIFIKAT BANK INDONESIA SYARIAH, PASAR UANG ANTAR BANK, PASAR UANG ANTAR BANK SYARIAH, FINANCE TO DEPOSIT RATIO DAN LOAN TO DEPOSIT RATIO - Achmad Adnan Fauzi Wicaksana; Raditya Sukmana (Universitas Airlangga, 2018)
This study aims to examine the effect of monetary policy transmission through conventional and sharia systems to the inflation rate in Indonesia from January 2011 to December 2015. The approach used is Vector Error Correction Model (VECM)quantitative method using Eviews 8 program. The data used was secondary data from the official website of Bank Indonesia and the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The result of the research shows that in the long run, conventional monetary policy transmission has aneffect on inflation rate in Indonesia, namely the interest rate of Bank Indonesia Certificates which has a positive and significant effect to the inflation rate in Indonesia. Interbank money market variables have negative and significant influence on the inflation rate. While the loan to deposit ratio variable doesn't have any effect on inflation rate. On the sharia side, the results show that in the long run, the sharia monetary policy transmission has an effect on inflation in Indonesia, namely Bank Indonesia Sharia Certificate that has significant negative effect and sharia money market has significant positive effect,whilst finance to deposit ratio doesn't. REFERENCESAjija, S. R. 2011. Cara Cerdas Menguasai EViews.Salemba Empat. JakartaAnshori, M. dan Iswati, S. 2009. Buku Ajar Metodologi Penelitian Kuatitatif. Surabaya: Airlangga University Press.Capra. 2000. Sistem Moneter Islam, Terjemahan oleh Ikhwan Abidin Basri.Cahyono, Ari. 2009. Pengaruh Indikator Makroekonomi Terhadap Dana PihakKetiga Dan Pembiayaan Bank SyariahMandiri. Tesis. UniversitasIndonesiaKarim, Adiwarman A. 2001. Ekonomi Islam: Suatu Kajian Kontemporer. Jakarta: Gema Insani PressMustafa, Edwin .2007. Pengenalan Eksklusif Ekonomi Islam Jakarta: Kencana Prenada Media GroupRahardjo, Prathama dan Manurung, Mandala. 2001. Teori Ekonomi Makro , Penerbit Fakultas Ekonomi Universitas IndonesiaaRusydiana, Aam S, 2009 Mekanisme Transmisi Syariah Pada Moneter Ganda di IndonesiaSugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&B. Bandung: Alfabeta.Warjiyo, P dan J. Agung. 2002. Transmission Mechanism of Monetary Policy in Indonesia. Directorate of Economic Research and Monetary Policy. Bank Indonesia, Jakarta.Triono, Dwi Condro. 2003. Pertumbuhan Ekonomi Versus Pemerataan Ekonomi. Irtikaz. Yogyakarta.